PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN PROSES PEMBELAJARAN DAN HASIL BELAJAR IPS KELAS IV.A SD NEGERI 79 PEKANBARU - Susi Yanti; Hamizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the low learning outcomes IPS CLASS IVA SDN 79 Pekanbaru because the model used by the teacher in the learning process is less precise because the IPS given less precise characteristics of the learning ips is a real experience and discovery. based on the problems it is necessary to find a way to solve using problem-based learning model, and improve learning activities with everyday life that can improve learning outcomes IPS.Subjek in this study were fourth grade students of SDN 79 Pekanbaru the number of students 20 people. This research was conducted in two cycles, cycle 1 held two meetings with the repetitions end of the cycle, and the second cycle was also conducted two meetings with one end siklus.Instrumen replicates data collection in this study is the end of the cycle repeat test and student observation sheet , teacher observation sheet. The study is in the form of classroom action research (PTK), this study aims to improve learning outcomes IPS. The results showed that problem-based learning model can improve student learning outcomes IPS, on the basis of a score of 66.50 has increased the average value in the first cycle class average value of 75.50 and the second cycle increased by a margin 85.50 increase base score to the first cycle of 10 points. In the teacher activity increased from the first first meeting first cycle of 60%, the second meeting of the second cycle increased to 75%. The second meeting of the second cycle increased to 80%, and the second meeting of the second cycle increased to 85% .In the first meeting student activity by 60% the first cycle, the second meeting of the first cycle to 70%. whereas at the first meeting of the second cycle of 80% and at the second meeting of the second cycle increased to 90% .This means of problem-based learning model can improve learning outcomes IPS IV.A grade students of SD Negeri 79 Pekanbaru.Keywords : Implementation Model Problem Based Learning, Learning Process and Learning Outcomes IPS